2016
DOI: 10.1002/etc.3666
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and mineralization of isotopically labeled TNT and RDX in anaerobic marine sediments

Abstract: The lack of knowledge on the fate of explosive compounds 2,4,6-trinitrotoluene (TNT) and hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), particularly in marine ecosystems, constrains the application of bioremediation techniques in explosive-contaminated coastal sites. The authors present a comparative study on anaerobic biodegradation and mineralization of N-nitro group isotopically labeled TNT and RDX in organic carbon-rich, fine-grained marine sediment with native microbial assemblages. Separate sediment slur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Elevated TOC level generated lower redox potential in sediment via TOC mineralization by natural microbial assemblages and also promoted microbially mediated anaerobic degradation of both DNAN and NTO via reduction and deamination (Krzmarzick et al, 2015;Mark et al, 2016;Temple et al, 2018). Removal under the iron-and sulfate-reducing conditions has been previously reported for legacy munitions, including TNT and RDX (Ariyarathna et al, 2017;Cho et al, 2012;Moser & Nealson, 1996). In the present study we observed similar links for DNAN and NTO removal in biotic incubations.…”
Section: Biotic Removal Of Dnan and Nto In Freshwater Sediment Incuba...supporting
confidence: 87%
See 1 more Smart Citation
“…Elevated TOC level generated lower redox potential in sediment via TOC mineralization by natural microbial assemblages and also promoted microbially mediated anaerobic degradation of both DNAN and NTO via reduction and deamination (Krzmarzick et al, 2015;Mark et al, 2016;Temple et al, 2018). Removal under the iron-and sulfate-reducing conditions has been previously reported for legacy munitions, including TNT and RDX (Ariyarathna et al, 2017;Cho et al, 2012;Moser & Nealson, 1996). In the present study we observed similar links for DNAN and NTO removal in biotic incubations.…”
Section: Biotic Removal Of Dnan and Nto In Freshwater Sediment Incuba...supporting
confidence: 87%
“…Sediments provide zones for more favorable removal of munitions constituents than overlying water (Ariyarathna et al, 2017; Smith et al, 2013). Flask‐scale studies show that the nitro groups of DNAN and NTO can be reduced in sediments, forming amino products that serve as principal degradation products of these IHE constituents (Fida et al, 2014; Krzmarzick et al, 2015; Olivares et al, 2016; Perreault et al, 2012; Schroer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using marine mesocosms, Tobias, Vlahos, and co-workers performed a series of experiments tracking the fate of 15 N-TNT and 15 N-RDX into the various nitrogen pools, macro and microbiota. Although it is difficult to directly compare among different systems and different mineralization methods, with roughly 400 μg of RDX L –1 added at day 1 and 6% mineralized by day 21, the mineralization rate estimate of ca. 1 μg of RDX L –1 day –1 to N 2 is comparable to the Rmin rates to CO 2 in coastal waters measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the control microcosm, bottles were autoclaved again after addition of inocula, and finally RDX was added in the autoclaved bottles. Microcosm bottles were completely wrapped with aluminum foil to avoid photo-degradation of RDX [ 36 ]. The final pH was 7.1 ± 0.2.…”
Section: Methodsmentioning
confidence: 99%